1968
DOI: 10.1113/jphysiol.1968.sp008405
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of the T‐system along the sarcomeres of frog and toad sartorius muscles

Abstract: SUMMARY1. Frog and toad sartorius muscles were soaked in ferritin suspensions and then fixed and prepared for electron microscopy. Ferritin particles were counted in micrographs of regions where fibril striations were in good register, and the number of particles plotted according to position along the sarcomeres.2. The distribution of ferritin particles in both frog and toad muscle sarcomeres could be accounted for by a single peak centred at the Z-line, with a total width of about 0*4 ut.3. The peak in toad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

1968
1968
1983
1983

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 16 publications
(23 reference statements)
1
28
1
Order By: Relevance
“…A continuous tubule could result from the repeated caveolation. In addition, the developed T system in vivo is much more curved and branched than had generally been believed (see Peachey and Schild, 1968). It seems that the T-system tubules are straight only where they are connected with the SR membranes, i.e.…”
Section: Discussionmentioning
confidence: 70%
“…A continuous tubule could result from the repeated caveolation. In addition, the developed T system in vivo is much more curved and branched than had generally been believed (see Peachey and Schild, 1968). It seems that the T-system tubules are straight only where they are connected with the SR membranes, i.e.…”
Section: Discussionmentioning
confidence: 70%
“…Since R 1 was calculated as being proportional to the T-system volume per unit fiber cross-section area in the lattice plane, to make R 1 equal to the resistivity of Ringer the T-system volume would have to be over three times lower than the value used. Although Peachey and Schild (1968) found that the fraction of the T-system volume accessible to ferritin might be as low as one-third, their estimate of the ferritin volume was a lower limit and they concluded that the entire T-system is probably accessible to ferritin and, therefore, presumably also to extracellular fluid. A high tubule internal resistivity would be consistent with the finding that the effective space constant of the T-system is shorter than can be explained on the basis of the tubule contents having the resistivity of Ringer solution (Adrian, Costantin, and Peachey, 1969).…”
Section: Imentioning
confidence: 99%
“…EDL and SOL muscles were examined at 11 age points : newborn, 2,3,5,7,10,15,20,30,40, and 60 days old. The muscles were dissected and fixed slightly stretched on cork blocks in 6.2% glutaraldehyde in 0.1 M cacodylate buffer (pH 7 .2) containing 2 mm CaCI2 (26), washed in buffer with 10% added sucrose, and postfixed in 1 % osmium tetroxide with 2 mm CaC12 . In some cases the tissue was stained en bloc with uranyl acetate (18) .…”
Section: Methodsmentioning
confidence: 99%